The Cambridge companion to the Talmud and rabbinic literature - Fonrobert, Charlotte Elisheva; Jaffee, Martin S. (Cambridge ; New York : Cambridge University Press, 2007)
This companion guides beginning students of rabbinic literature to the range of historical-interpretive and culture-critical issues that contemporary scholars use when studying the rabbinic texts of late antiquity.
Rabbinic authorship as a collective enterprise / Martin S. Jaffee -- The orality of rabbinic writing / Elizabeth Shanks Alexander -- Social and institutional settings of rabbinic literature / Jeffrey L. Rubenstein -- The political geography of rabbinic texts / Seth Schwartz -- Rabbinic midrash and ancient Jewish biblical interpretation / Steven D. Fraade -- The Judaean legal tradition and the halakhah of the Mishnah / Shaye J.D. Cohen -- Roman law and rabbinic legal composition / Catherine Hezser -- Middle Persian culture and Babylonian sages : accommodation and resistance in the shaping of rabbinic legal tradition / Yaakov Elman -- Jewish visionary tradition in rabbinic literature / Michael D. Swartz -- An almost invisible presence : multilingual puns in rabbinic literature / Galit Hasan-Rokem -- The "other" in rabbinic literature / Christine Hayes -- Regulating the human body : rabbinic legal discourse and the making of Jewish gender / Charlotte Elisheva Fonrobert -- Rabbinic historiography and representations of the past / Isaiah Gafni -- Rabbinical ethical formation and the formation of rabbinic ethical compilations / Jonathan Wyn Schofer -- Hellenism in Jewish Babylonia / Daniel Boyarin.
Includes bibliographical references (p. 365-392) and indexes.
Keywords: Talmud -- Criticism, interpretation, etc; Rabbinical literature -- History and criticism; Jewish law -- History -- To 1500.